The Importance of the Development of Inclusive Material (Revista Electrónica Calidad en la Educación Superior, 2022)
Teaching materials or resources correspond to the means used to facilitate interaction between all learners and the reality of the learning process. Here we highlight all learners because it is important to include students with a disability or special need. Listed in the background of the Uniform Norms on Equal Opportunities (OHCHR, 2021, p. 3), it indicates that people with disabilities exist throughout the world and at all levels, which is increasing. The materials are important, they serve as a link between the contents and the procedures, added to this importance, of considering the relevant aspects to craft or develop them in an inclusive way. The videos prepared by the UNED on the Universal Design of Learning are an example to be followed. This work is a demonstration of a diagnostic test used as an example of a material prepared with an inclusive intention.
Keywords: Inclusive Materials; Inclusive; Usability; Flexibility; Mobility; Evaluation